Effect of Flow Regime on Total Interfacial Area of Two Immiscible Fluids in Microchannel Reactor Using VOF Model - Laziz, A.M. (Springer, 2020)
The application of microfluidic in chemical processing, for example, the microchannel reactor has received much attention. This type of reactor can enhance the reaction efficiency due to high total interfacial area for the interaction of reactants in a multiphase reaction. The behavior of multiphase flow can create several different types of regimes such as segmented, annular, or droplet flow, depending on the flow conditions between the two immiscible liquids. The droplet flow has relatively higher total interfacial area than the annular flow. Depending on the total volumetric flow rate and volumetric ratio, the size of the microdroplet can be varied. In this study, the size of the microdroplet is investigated by varying the volumetric ratio of oil-to-methanol, O/M, and the total volumetric flowrate, QTotal. Computational fluid dynamics (CFD) method using Volume of Fluid (VOF) model is implemented to predict the size of the microdroplet produced in the microchannel reactor. In addition, the model is first validated with the experimental data which showed good agreement between numerical and experimental results. It was found that the droplet size is decreasing as the total volumetric flow rate and oil-to-methanol ratio increases, which will increase the total interfacial area. In addition, droplet regime has the highest total interfacial area, while segmented regime has the lowest total interfacial area. This finding is useful especially in designing a microreactor that controls the size of droplet and maximizes the total interfacial area, overall enhancing the reaction process. Â© 2020, Springer Nature Singapore Pte Ltd.